2001
DOI: 10.1046/j.1468-3083.2001.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Tinea barbae associated with erythema nodosum in an immunocompetent man

Abstract: We describe the case of a 45-year-old man with atopy who developed marked inflammatory lesions on the bearded area of the face caused by Tricophyton rubrum, an anthropophilic fungus not frequently correlated with kerion of the face. After starting therapy with griseofulvin, he developed typical lesions of erythema nodosum on both legs. We discuss how these lesions could be correlated with the kerion of the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Only 13 cases have been reported in the international literature, occurring in patients aged between 3 and 19 years and in one man aged 45 years. T. mentagrophytes was identified in 8 of the 13 cases; Trichophyton gypseum, Trichophyton sulphureum, Trichophyton rubrum, Trichophyton verrucosum and Epidermophyton floccosum were found in the remaining 5 (1 case each) 2–5 …”
mentioning
confidence: 99%
“…Only 13 cases have been reported in the international literature, occurring in patients aged between 3 and 19 years and in one man aged 45 years. T. mentagrophytes was identified in 8 of the 13 cases; Trichophyton gypseum, Trichophyton sulphureum, Trichophyton rubrum, Trichophyton verrucosum and Epidermophyton floccosum were found in the remaining 5 (1 case each) 2–5 …”
mentioning
confidence: 99%
“…A patient with characteristics of erythema nodosum and skin coccidiomycosis of hypodermis was described by Blair (2007). Epidermophyton floccosum infection (Provini et al, 2003), Trichophyton mentagrophytes and Trichophyton rubrum infections during the course of scalp mycoses of a kerion type (Calista et al, 2001;Foti et al, 2001) have been described less frequently. Blaise et al (2007) reported on a viral infection caused by parvovirus B19 and a reactive erythema nodosum-like manifestation.…”
Section: Discussionmentioning
confidence: 99%